KEPEMIMPINAN TECHNOPRENEUR SEBAGAI PENGGERAK LITERASI DIGITAL DAN INOVASI PEMBELAJARAN DI KOTA BOGOR - Rahmawati, Ima; Lestari, Hana; Dafenta, Hadi; Rinawati (Institut Agama Islam Sahid (INAIS) Bogor, 2025)
This study aims to analyze technopreneurial leadership as a driver of digital literacy and learning innovation in Bogor City. A mixed-method approach was employed by integrating quantitative and qualitative data. Quantitative data were collected from 60 teachers selected through stratified random sampling and analyzed using linear regression to examine the relationship between technopreneurial leadership, digital literacy, and learning innovation. Qualitative data were obtained through in-depth interviews with 15 key informants consisting of school principals, supervisors, lecturers, and education practitioners to enrich the understanding of leadership practices in the field. The findings reveal that technopreneurial leadership significantly enhances teachers’ digital literacy and supports the development of innovative, technology-based learning models. Visionary, adaptive, and innovative leadership practices were shown to strengthen a collaborative digital education ecosystem. This study highlights that strengthening technopreneurial leadership capacity within educational institutions is a strategic factor for fostering a sustainable innovation culture. The results can serve as a reference for developing training programs, formulating educational policies, and fostering cross-sectoral collaborations to advance digital transformation in education.